The effect of an aggressive behavior prevention program on kindergarten students - ERGÜN, AYŞE (WILEY, 2019)
Objectives This quasi-experimental study with a pretest-posttest control group was conducted to determine the effects of the Aggressive Behavior Prevention Program (ABPP) on kindergarten students. The program was based on Social Cognitive Theory. Design and Sample The study was carried out with 90 children (intervention group = 45, control group = 45) who were registered in the kindergarten of a primary school. The ABPP was implemented with children and their families for 12 weeks. Data were collected with a subscale of Aggressiveness of the Eyberg Child Behavior Inventory, the subscales of overt and relational aggression of the Preschool Social Behavior Scale-Teacher Form, and the Victimisation Scale. Results The ABPP significantly decreased levels of aggression among kindergarten students (p = 0.019). No significant difference was found between the two groups for peer victimization. Conclusions This is the first study in Turkey implemented by a nurse based in school and it is important because it offers an example for nurses' practice and research. Findings suggest that the ABPP is effective in reducing the aggression of children.
Keywords: aggressive behavior; child; preschool; PARENTING PROGRAM; SCHOOL; RISK